The microbiota changes of the brown dog tick, Rhipicephalus sanguineus under starvation stress - An, Liping; Bhowmick, Biswajit; Liang, Dejuan; Suo, Penghui; Liao, Chenghong; Zhao, Jianguo; Han, Qian (Frontiers in Physiology, 2022)
Rhipicephalus sanguineus, the brown dog tick, is the most widespread tick in the world and a predominant vector of multiple pathogens affecting wild and domestic animals. There is increasing interest in understanding the role of tick microbiome in pathogen acquisition and transmission as well as in environment–vector interfaces. Several studies suggested that the tick microbial communities are under the influence of several factors including the tick species, dietary bloodmeal, and physiological stress. Compared with insects, very little of the microbial community is known to contribute to the nutrition of the host. Therefore, it is of significance to elucidate the regulation of the microbial community of Rh. sanguineus under starvation stress. Starvation stress was induced in wild-type adults (one month, two months, four months, six months) and the microbial composition and diversity were analyzed before and after blood feeding. After the evaluation, it was found that the microbial community composition of Rh. sanguineus changed significantly with starvation stress. The dominant symbiotic bacteria Coxiella spp. of Rh. sanguineus gradually decreased with the prolongation of starvation stress. We also demonstrated that the starvation tolerance of Rh. sanguineus was as long as six months. Next, Coxiella-like endosymbionts were quantitatively analyzed by fluorescence quantitative PCR. We found a pronounced tissue tropism in the Malpighian tubule and female gonad, and less in the midgut and salivary gland organs. Finally, the blood-fed nymphs were injected with ofloxacin within 24 hours. The nymphs were allowed to develop to adults. It was found that the adult blood-sucking rate, adult weight after blood meal, fecundity (egg hatching rate), and feeding period of the newly hatched larvae were all affected to varying degrees, indicating that the removal of most symbiotic bacteria had an irreversible effect on it.